Fraud Pentagon Model: Predicting Student’s Cheating Academic Behavior - Iqbal Lhutfi; Raden Dian Hardiana; Rika Mardiani (Jurnal ASET (Akuntansi Riset), 2021)
This study was conducted to detect academic fraud in students using the fraud pentagon approach. The research method used in this research is the descriptive and verification method. The subjects in this research are Accounting Education students consisting of several State Universities that are members of the Indonesian Accounting Educator Professional Alliance (APRODIKSI). The main data needed in this study is data derived from questionnaires distributed via google form to maintain health protocols during the pandemic. The questionnaire was distributed after previously being tested for validity and reliability for each question item in the questionnaire using Statistical Product and Service Solutions (SPSS) software. Furthermore, the data collected analyzed by descriptive method. This study concludes that the role of fraud pentagon approach is important in detecting student fraud, plus other contributing factors such as external pressure and also gender which determines students when committing academic fraud. Through this research, it can be seen the predictive factors that are the reasons students commit fraud so that it can be easy for educational institutions to find the right way to prevent it.